Accuracy of thermal microsensors embedded in orthodontic retainers of different material composition and thickness: An in vitro study - Wafaie Khaled; Mohammed Hisham; El Sergani Ahmed M.; Almagrami Ibtehal; Qaisi Ahmed G.; Yiqiang Qiao (Sciendo, 2023)
Objectives: The present research aimed to assess the accuracy and precision of the TheraMon® microsensor embedded in different thicknesses of Hawley retainers (HR) for comparison with vacuum formed retainers (VFR).